Penerapan Senam Hipertensi pada Tekanan Darah Lansia di Wilayah Kota Surakarta - Yulianita Rahmawati; Ida Nur Imamah (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Elderly is someone aged 60 years and over. Factors causing hypertension are genetics, an unhealthy lifestyle. WHO in 2021 the number of hypertension sufferers will double to 1.28 billion due to population and aging in the world. One of the efforts made to lower blood pressure is hypertension exercise. Objective: To determine the effectiveness of hypertension exercise on the blood pressure of elderly in the Surakarta city area. Method: Descriptive with application to 2 respondents. Respondents had their blood pressure measured 10 minutes before doing the exercise, then they were given exercise for 30 minutes, once a week for 3 weeks, and their blood pressure was measured 15 minutes after doing the exercise. Results: After applying hypertension exercises for 3 weeks, it was found the average blood pressure of Mrs.S before the exercise was 144/93 mmHg, and Mrs.W is 148/97 mmHg. Then the average blood pressure of Mrs.S after doing the exercise was 133/89 mmHg, and Mrs.W is 133/90 mmHg. Conclusion there was a decrease in blood pressure before and after being given hypertension exercises in respondents, result of a decrease in Mrs.S's blood pressure by 11/4 mmHg and Ny.W's blood pressure by 15/7 mmHg.